1995
DOI: 10.1084/jem.182.6.1985
|View full text |Cite
|
Sign up to set email alerts
|

Expression of costimulatory molecules B7-1 (CD80), B7-2 (CD86), and interleukin 12 cytokine in multiple sclerosis lesions.

Abstract: SummaryResting autoreactive T cells are present in the circulation ofnormal individuals without pathologic consequences . In autoimmune animal models, stimulation of these self-reactive T cells in the presence of costimulatory molecules B7-1 results in T cell-mediated autoimmune disease, whereas B7-2 stimulation generates regulatory autoreactive T cells that abrogate disease severity . Thus, reactivation in the brain of myelin-autoreactive T cells by antigen with costimulatory molecules may be a critical event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
192
1
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(211 citation statements)
references
References 55 publications
17
192
1
1
Order By: Relevance
“…diseases, such as MSrEAE. Windhagen et al 1995 have evaluated expression of B7-1 and B7-2 in relation to IL-12 production in human MS brain. These authors found increased expression of B7-1 and IL-12p40 in acute MSplaques, particularly from early disease cases.…”
Section: Accessory Molecules: B7-1 R B7-2mentioning
confidence: 99%
“…diseases, such as MSrEAE. Windhagen et al 1995 have evaluated expression of B7-1 and B7-2 in relation to IL-12 production in human MS brain. These authors found increased expression of B7-1 and IL-12p40 in acute MSplaques, particularly from early disease cases.…”
Section: Accessory Molecules: B7-1 R B7-2mentioning
confidence: 99%
“…In this capacity, IL-12 plays a key role in the defense against intracellular microorganisms. In addition, excessive IL-12 production has been found in several organ-specific autoimmune diseases, including rheumatoid arthritis, 5 type I diabetes mellitus, 6 multiple sclerosis (MS) 7 and Crohn's disease (CD). 8 The latter are associated with a strong genetic component in disease susceptibility, which renders the possibility that genetic alterations in the genes affecting the height of the IL-12 response are involved in the susceptibility to autoimmune as well as infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of IL-12 in the CNS is found in a number of immunoinflammatory states including multiple sclerosis (MS) 5 (4), experimental allergic encephalomyelitis (EAE) in rats (5) and in mice (6), and in murine endotoxemia (7,8). Besides being produced by CNS-infiltrating immune cells, IL-12 can be produced by neural cells including microglia (7)(8)(9)(10) and astrocytes (8,11).…”
mentioning
confidence: 99%